Urban Planning Against The Urban. City and Urban Life in Henri Lefebvre - Delgado Ruiz, Manuel (2017)
Henri Lefebvre’s theory about urban life is based on the pivotal opposition between the space which is lived by those who use it or dream about it, and the abstract space that city technocrats would like to organize –even if they are rarely aware of the extent to which their “creativity” is subjected to private or institutional interests. Behind this hypothetical space in which city planners and architects work is pure ideology, the ghost that covers and disguises real social relations of production. Facing -or even ignoring- that merely theoretical spatial order of the “experts”, cities experience a constant and imminent activity that has to be understood as the apotheosis or essence of social relations. The urban is characterized by an intrinsic dynamism, always spun by developments and occurrences on which the “experts” implement plans and projects, even if they really ignore its real character - perhaps, this is the reason why they constantly try to deny it.